Simulation and Analysis of Multiphase Flow in a Novel Deepwater Closed-Cycle Riserless Drilling Method With a Subsea pump+gas Combined Lift - Wang, Jintang; Sun, Jinsheng; Xie, Wenwei; Chen, Haowen; Wang, Cai; Yu, Yanjiang; Qin, Rulei (Frontiers in Physics, 2022)
Recently, deepwater resource exploration has grown rapidly. Because the conditions of marine environment and seabed geology are more complex, deepwater drilling needs to numerous confront challenges, such as more complicated wellbore situations, low drilling efficiency, and high cost. Advanced novel drilling methods serve as significant impetus to facilitate the rapid advancement in deepwater oil-and-gas exploration and development. However, adopting riserless drilling methods may pollute marine environment and yield poor wall protective effects, while drilling methods with risers may suffer from relatively high cost and risk. Based on these dilemmas, in this study, a novel deepwater closed-cycle riserless drilling method with a subsea pump + gas combined lift is proposed. The proposed novel closed-cycle method has also established a multiphase flow drilling model and analyzed the effects of drilling fluid displacement, gas injection displacement, gas injection site and seawater depth on the multiphase flow in the wellbore. The simulation results revealed the following: As the gas migrates upward along the pipeline, its flow velocity first increases slowly and then rapidly owing to the volume expansion of gas. Larger displacement of drilling fluid demands greater working power of the subsea lifting pump, which is characterized by a nonlinear relationship. The gas injection displacement can effectively mitigate the load-bearing capacity of the pump, and increasing gas injection displacement leads to a decreased subsea lifting pump working power requirement; the decreasing effect on pump power load is more significant in the case of low gas injection displacement. Increasing the depth of gas injection sites reduces the subsea pump working with a decreasing slope with respect to the power descent. Finally, the subsea pump lifting power demand increases approximately linearly with an increasing seawater depth. Subsequently, an optimization method of hydraulic parameters for deepwater closed-cycle riserless drilling was proposed, which provides a theoretical foundation for the selection of subsea pumping power as well as the optimization of gas injection sites and displacement.